The cultural construction of Chinese universities based on the perspective of Confucian cultural practice - Haixin, L (2022)
Culture is a source of national cohesion and creativity. In the context of China's national political orientation and higher education development, it has become increasingly important to address the formation of university campus culture, as both a link to cultural tradition and a basis for educating people in the present. The development of Chinese universities has been influenced on the one hand by Chinese culture, especially Confucian culture, and on the other hand by Western universities. However, the integration of Chinese culture and education in universities has not been ideal. Almost all Chinese universities have transplanted higher education systems from the Western English-speaking world, and most of them have not yet formed their own characteristics in development and governance. Hence the role and nature of traditional practices, and their relationship with Western practices, is a subject of great significance in the evolution of Chinese higher education. This dissertation investigates the practice of Confucian culture in universities in China and reviews the cultural origin, construction and improvement of Chinese universities. This study starts with the concepts of Confucian culture and Chinese university campus culture. It then sets down the methodology, which rests on an interpretive epistemology and constructivist approach. The study combines literature-based research and archival research methods, with qualitative interviews in two universities where understanding of Confucian ideas is relatively advanced: Peking University and Qufu Normal University. The researcher conducted semi-structured interviews with eight staff from these two institutions. Three levels of coding and text analysis were carried out in relation to the primary data. The study finds that both Chinese and Western practices emphasized similar functions of university education in the development of Chinese universities. However there was also a collision between Confucian family-based working structures and academic independence, and a conflict between Confucian values of moderation and Western ideas of competition and innovation. The study goes on to summarize the role of Confucian cultural practices in Chinese universities, in relation to teaching and learning, the campus environment, and organization and management. Looking at the specific practices of Peking University and Qufu Normal University, it identifies beneficial attempts to integrate Confucian culture into Chinese universities, including the establishment of Confucian research institutes (see Appendix H and I), and the integration of Confucian culture into classes and practical activities. At the same time, it also reflects on a series of problems that have arisen. Some college students have little sense of identity with Confucian culture, and the connection between Confucian culture and the curriculum is not always well established. Finally, based on the above findings, this study discusses how to improve the contribution of Confucian cultural practice in Chinese universities.